Burkitt’s lymphoma - Tınaztepe, Behçet; Işık, Türkiz; Tınaztepe, Keriman (The Turkish Journal of Pediatrics, 1973)
Clinical and pathological aspects of 20 cases of Burkitt’s tumor diagnosed in the Department of Pediatric Pathology of Hacettepe Children’s Hospital are reviewed. Similar and dissimilar features are compared with Burkitt’s tumor in African children.